Reprogramming to cancer induced pluripotent stem cells elucidates the contribution of genetic and epigenetic alterations to breast carcinogenesis - Leong, Yeh Chwan (2018)
The induced pluripotent stem cells (iPSCs) technology has revolutionized disease modelling by enabling the generation of patient-specific pluripotent stem cells for the study of complex disorders such as cancer. Somatic cell reprogramming through iPSCs induces global epigenetic reconfiguration of the chromatin which converts cancer cells to an embryonic stem cell-like state with potential reversion of tumorigenicity. Therefore, reprogramming can be used to answer the question as to whether epigenetic alterations alone can be sufficient to induce carcinogenesis, independent of genetic defects. In addition, it can used to dissect the relative contribution of genetics and epigenetics and epigenetics to tumorigenicity. In this study, the triple negative breast cancer (TNBC) cell line BT-549 and oestrogen receptor positive (ER+) cell line MCF7 were successfully reprogrammed by using the non-integrative episomal vectors expressing OCT4, SOX2, L-MYC, KLF4, LIN28, EBNA1, shRNA against TP53, and microRNA-302/367 cluster together with treatment of sodium butyrate. Pluripotency of cancer-derived iPSCs was confirmed by RT-PCR, RT-qPCR and immunofluorescence staining for expression of pluripotency markers. Differentiation potential of iPSCs was also assessed by using in vitro differentiation either spontaneous or directed to the mammary lineage. Functional assays indicated potential loss of tumorigenicity in re-differentiated cells derived from cancer iPSCs. The same approach was applied to study an immortalised, non-malignant mammary epithelial cell line MCF10A and two of its derived isogenic lines harbouring the two most frequent mutations in breast cancer, PIK3CAH1047R (+/-) and TP53(-/-), created by using CRISPR-Cas9 gene editing. Reprogramming induced a tumorigenic phenotype in iPSCs (PIK3CAH1047R (+/-) isogenic line only) and re-differentiated progenies (in both wild type MCF10A and PIK3CAH1047R (+/-) cell lines), suggesting the contribution of PIK3CA mutation in enhancing malignant transformation. Results in this study suggested that epigenetics alone and/or its interaction with genetic defects (e.g. PIK3CA mutation) has significant impact on breast cancer carcinogenesis. The dissection of the molecular mechanisms underlying the loss and gain of tumorigenicity using the iPSC models generated in this study could provide general understandings on breast carcinogenesis, which in turn could have important clinical implications.